2018
DOI: 10.1161/jaha.118.010797
|View full text |Cite|
|
Sign up to set email alerts
|

Preconception Exposure to Fine Particulate Matter Leads to Cardiac Dysfunction in Adult Male Offspring

Abstract: Background Particulate matter (particles < 2.5 μm [ PM 2.5 ]) exposure during the in utero and postnatal developmental periods causes cardiac dysfunction during adulthood. Here, we investigated the potential priming effects of preconception exposure of PM 2.5 on cardiac function in adult offspring. Methods and Results Male and female friend leukemia virus b (FVB) mice were exposed to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…The interactions represent direct, validated experimental associations between genes that were increased (red), decreased (green), or found to have a diverse expression profile (yellow) following exposures. All abbreviations are defined in GLOSSARY. in 3-mo-old progeny (148). Inflammatory and oxidative pathways are thereby activated, resulting in increased IL᎑6, IL᎑15, NF-B, and CRP, along with elevated fibrosis (Col3a1), similar to the results found in many direct exposure studies.…”
Section: Oxidative Stress and Inflammationsupporting
confidence: 81%
See 2 more Smart Citations
“…The interactions represent direct, validated experimental associations between genes that were increased (red), decreased (green), or found to have a diverse expression profile (yellow) following exposures. All abbreviations are defined in GLOSSARY. in 3-mo-old progeny (148). Inflammatory and oxidative pathways are thereby activated, resulting in increased IL᎑6, IL᎑15, NF-B, and CRP, along with elevated fibrosis (Col3a1), similar to the results found in many direct exposure studies.…”
Section: Oxidative Stress and Inflammationsupporting
confidence: 81%
“…This further suggests the ability of gestational PM exposure to induce global epigenetic remodeling through transcriptional activation of acetylated regions in offspring. Supporting these findings, multiple additional studies have reported a cardiac hypertrophic/fibrotic phenotype, cardiac functional changes, and epigenetic reprogramming in early development due to gestational PM exposure (148,150,169). Preconception exposure in both parents to PM 2.5 resulted in progeny with decreased ejection fraction, fractional shortening, and cardiomyocyte contractility at 12 wk of age (148).…”
Section: Epigenetics and Transcriptional Regulationmentioning
confidence: 73%
See 1 more Smart Citation
“…More importantly, maternal exposure to ambient PM 2.5 during the third trimester of pregnancy was associated with elevated blood pressure in children aged 3 to 9 years 24 . Exposure to PM 2.5 during preconception, 25 in utero, and early life development in mice increased cardiac abnormalities or aggravated susceptibility to heart failure 26 . Although these studies found that maternal exposure to ambient PM 2.5 was associated with offspring hypertension, the effects of parental PM 2.5 exposure on susceptibility of offspring to air pollution was lacking.…”
Section: Discussionmentioning
confidence: 98%
“…23 More importantly, maternal exposure to ambient PM 2.5 during the third trimester of pregnancy was associated with elevated blood pressure in children aged 3 to 9 years. 24 Exposure to PM 2.5 during preconception, 25 in utero, and early life development in mice increased cardiac abnormalities or aggravated susceptibility to heart…”
Section: Discussionmentioning
confidence: 99%